2020
DOI: 10.20870/oeno-one.2020.54.4.3361
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard yield estimation using 2-D proximal sensing: a multitemporal approach

Abstract: Vineyard yield estimation is a fundamental aspect in precision viticulture that enables a better understanding of the inherent variability within a vineyard. Yield estimation conducted early in the growing season provides insightful information to ensure the best fruit quality for the maximum desired yield. Proximal sensing techniques provide non-destructive in situ data acquisition for yield estimation during the growing season. This study aimed to determine the ideal phenological stage for yield estimation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Syrah. The good agreement between these bunch features and bunch weight was similar to the results presented in previous research [1,34], but, to the best of our knowledge, have never been used together in the same estimation model.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Syrah. The good agreement between these bunch features and bunch weight was similar to the results presented in previous research [1,34], but, to the best of our knowledge, have never been used together in the same estimation model.…”
Section: Discussionsupporting
confidence: 88%
“…As mentioned before, all of the analyzed features could be collected from a vine image of a realistic, vineyard scenario [12,15,34,37]. However, we predict that the application of the studied approach in such conditions would be subject to several challenges/adaptations, such as (i) image resolution, which would be particularly important to extract features such as bunch perimeter and visible berries, as these require more detail and, thus, higher resolution if images are to be taken from a larger distance; (ii) bunch occlusion by leaves, where recent works have explored ways to estimate the occluded bunches [39,40], but this challenge still remains unsolved; (iii) extracting features from occluded bunches, as even if occluded bunches are estimated, it will be impossible to have their corresponding exact area, visible berries or perimeter, and ratios between these features on the visible portion of the bunches can be a better option; and (iv) robust segmentation methods, as this challenge lies in the step before the weight estimation (segmentation step), being crucial for a vineyard scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The first reason is, again, related to differences in bunch morphological traits (OIV, 2009). An example of such a trait is bunch compactness, which has been mentioned in several works as a possible cause of error in bunch weight estimation using image analysis (Aquino et al, 2018b;Hacking et al, 2020). Although this trait changes with different varieties, it can also change with different management practices, flowering and fruit-set conditions and even water availability (Tello and Ibáñez, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, in natural conditions, in general, yield components are not all visible to the scanning sensors, requiring manual intervention (e.g., defoliation) or, alternatively, modelling approaches to estimate non-visible fruits. Regarding the most used yield components for yield estimations with image analysis, there are two main trends that have been explored in previous research: one uses the estimated number of visible berries in an image (Nuske et al, 2014b;Aquino et al, 2018a;Milella et al, 2019;Liu et al, 2020), the other uses bunch projected area or bunch pixels (Liu et al, 2013;Lopes et al, 2017;Hacking et al, 2020;Victorino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Grapevine yield estimation has been widely addressed using computer vision at different phenological stages, such as budbreak (Liu et al, 2017), flowering (Liu et al, 2018;Palacios et al, 2020), pea-size (Aquino et al, 2018;Liu et al, 2020;Palacios et al, 2021Palacios et al, , 2022, and harvest (Dunn & Martin, 2004;Liu et al, 2013Nuske et al, 2014b;Xin et al, 2020). A recent work (Hacking et al, 2020), concluded that the final stage of berry ripening was the ideal phenological stage for grapevine yield estimation. Information about the number of berries can lead to an adequate and early estimation of the yield in grapevine.…”
Section: Introductionmentioning
confidence: 99%